Assessment of floating marine debris density, composition, chemical characteristics, and recycling potential along Gajah Beach and Pasir Putih Tabing Beach, Padang City, Indonesia - Rizki Aziz; Budhi Primasari; Hirzan Salda Putra; Cici Amelia Edriani (Researcher and Lecturer Society, 2026)
Floating marine debris is one of the major environmental challenges affecting coastal ecosystems and marine activities. Accumulation of floating debris can interfere with fishing operations by increasing the amount of debris captured in fishing nets and reducing fishing efficiency. This study evaluated the density, composition, chemical characteristics, and recycling potential of floating marine debris along Gajah Beach and Pasir Putih Tabing Beach, Padang City, Indonesia. Floating marine debris was collected using fishing trawls under two environmental conditions: normal weather and one day after a rainfall event. Samples were collected from three sampling points representing the study area and analyzed for debris density, material composition, proximate characteristics, and recycling potential. The average debris density increased from 1.18 g/m² under normal weather conditions to 3.13 g/m² after rainfall. Five material categories were identified, namely plastic, wood, rubber, fabric, and coconut husk. Plastic was the dominant material, accounting for 90% of the debris under normal weather conditions and 50% after rainfall, with corresponding densities of 0.90 g/m² and 1.66 g/m², respectively. Proximate analysis showed average values of 25.05% moisture content, 56.33% volatile matter, 8.53% ash content, and 9.09% fixed carbon. The results also indicate that plastic, wood, fabric, and coconut husk have potential for recycling or resource recovery. These findings provide baseline information for marine debris monitoring and support the development of more effective coastal waste management and resource recovery strategies in Padang City.